Life Events and Adaptive Coping Approaches to Self-Management From the Perspectives of Hospitalized Cardiovascular Patients: A Qualitative Study - Qiu, Ruolin; Tang, Leiwen; Wang, Xiyi; Ye, Zhihong (Frontiers in Psychiatry, 2021)
Objectives: This study aimed to explore the association between hospitalized cardiovascular parents’ life events and adaptive coping approaches to self-management. Methods: The study was a qualitative study which was conducted in a Cardiology Department of one affiliated university hospital in Hangzhou, China. Twenty-eight participants with cardiovascular diseases were recruited through a purposive sampling procedure. Semi-structured interviews were used to gain insights into adaptive coping approaches to self-management when living with different life events. Interviews were audio-recorded and transcribed, and the data were analyzed by thematic analysis. Results: Life events reported by hospitalized cardiovascular participants could be summarized in four categories: daily routines, life changes, life-threatening experiences, and emotional sufferings. The adaptive coping approaches were also summarized in four themes: decision-making, avoidance, consistent responses, and episodic responses. Conclusions: This study described essential insights into the mutual influences between various life events and adaptive coping approaches to self-management by a group of hospitalized cardiovascular patients. Participants coped with their problems flexibly by processing comprehensive information from various and unpredictable life events regarding the situations and contexts. While inequity was cumulated, psychological resilience was a vital mediator between stressful events and their responses. The study illuminated the importance of understanding context, situations, and experiences about how cardiovascular patients adapted to their self-management regimens.